Health need assessment in female adolescents, in Qom: A cross sectional study - Zahra Alipour; Narges Eskandari; Sareh Sangi; Esmat Gafarbegloo; Hoda Ahmari Tehran; Zahra Aghvam Karbasi; Azam Bagheri (Journal of Education and Health Promotion, 2019)
BACKGROUND AND OBJECTIVE: Due to the young population of Iran, a significant number of teenagers in our country and the importance of the health of adolescents, especially teenage girls who are the mothers and the future-makers of the society, we designed this study to determine the health needs of adolescent girls living in the city of Qom. METHODOLOGY: In this descriptive cross-sectional study, the research population included 853 student girls in the middle and high secondary grades in the city of Qom selected and participated in the study through a randomized multistage cluster sampling method. Data were collected by completing the demographic information questionnaire, and the adolescent girls' health needs questionnaire. Data gathered were analyzed using SPSS software version 19 using the descriptive and inferential statistics. RESULTS: The study results showed that the scores of the adolescent girls' needs in health-related areas are as follows: health: 65.33 ± 22.08, nutrition: 52.81 ± 25.40, exercise and physical activity: 50.10 ± 30.55, social justice: 53.95 ± 23.82, counseling: 49.55 ± 34.97, school status: 52.69 ± 28.01, relationship with parents: 55.10 ± 27.44, social support: 50.64 ± 30.52, education: 51.88 ± 29.61, religious beliefs, and spirituality: 66.88 ± 20.87. CONCLUSION: Based on the results of this study, the adolescent girls have a lot of perceived needs in various areas of health, including psychological-emotional, social, physical, educational, and beliefs areas, which have not been met. Therefore, it is recommended to plan and carry out the necessary measures to meet the needs of adolescents with their participation and relevant authorities.